The Role of Heritage Decorations in Embellishing the Habitat : The Model of Mashrabya in Rawdat El Sayeda Zaynab - Abdellah Salem, Amina (Journal of Architecture and environment of child, 2023)
This study seeks to throw the light on the slums that have been altered to be eligible for appropriate living. The government has recently been concerned about demolishing slums and building new resident areas. Thus, the area of Tal El Akareb in Sayeda Zaynab, Cairo has been transformed from being slums (where buildings are made of stone and tin as well as palm leaf stalk or wooden ceilings) to an urban residential area which suits Rawdat Ela Sayeda Zaynab distinguished by the decorative inscriptions on the balconies in the form of mashrabeya. This motivates uncovering the influence of the popular heritage on the architecture in the contemporary housing of Tal El Akareb in general and the art of calligraphy in specific. This is done through highlighting the role of the calligraphy craft in architecture as a way of reviving the popular heritage and improving the habitat of the urban community. This study confirms that heritage gives the sense of civilization, art and sophistication and promotes the people of this area by restoring the folklore and exploits each craft to embellish the environment.